Strategic migration policy - HD.SMP 1.0 [research data] - Harnisch, Sebastian; Lujic, Tijana; Potinius, Katharina (Universität, 2023)
As part of the Strategic Migration Policy project, a dataset (HD.SMP 1.0) was developed that systematizes and codes bilateral migration agreements ...